The media, electoral campaign rallies and government's hypocrisy of physical distancing in the COVID-19 era: The Nigerian experience - Nwankpa, Nduka N; Umoren, Philomena E; Onwuka, Ngozi Amanda; Utuk, Princess Aniekan (American Journal of Leadership and Governance, 2022)
Purpose: In several democracies an electoral campaign rally is a direct contact communication tactic politicians and political parties adopt to present themselves and their programmes to the electorate, with the ostensible aim of persuading these targets to cast their ballot for the party and its candidate. Through the media these mass campaign gatherings are relayed to thousands of voters outside the venues of these events. In fact, in several instances regular programming on TV has been suspended for live coverage of campaign rallies sponsored by politicians and their parties. Mediated images of mammoth crowds converged at campaign grounds is an eloquent testimony of the mobilisation and management prowess of campaign managers of politicians at an election time. But in the COVID era, it is disturbing, not only because of the health risks posed by such large gatherings in defiance of the state-run NCDC established COVID-19 protocols on physical distancing, but more worrisome that the same governments that have mounted public enlightenment campaigns on measures to check the spread of COVID-19 using billions of donor funds, and have threatened to sanction violators of COVID-19 protocols (and have in certain cases made good their threat) are behind these mass campaign rallies where physical distancing rules are violated. Therefore, the study analyses the health and political implications of electoral campaign rallies using the 2020 governorship election campaign rallies in Edo and Ondo States as case studies. Methodology: A combination of semi-structured interview, personal observation and in-depth literature review was adopted to analyse the health and political implications of lawmakers becoming lawbreakers as it concerns the violation of public health rules in these campaigns by the incumbent governors of these states. Findings: It was found that rallies can cause a spike in infection in society, as the Edo case has confirmed. Results suggest that to these governors winning a second term came first before the lives of citizens, and that politics, it appears, supersedes every other protocol, including public health protocols in the pandemic. Hypocrisy and negligence are implicated as causal factors in the conduct of these two governors. It is believed that these have bred the mistrust between government and citizens in Nigeria. Unique Contribution and Recommendation: Digital electoral campaign is recommended to reduce physical contact that could endanger the health of citizens as a result of mass-attended election campaign rallies.